KONTRIBUSI EFIKASI DIRI DAN KONSEP DIRI TERHADAP KESIAPAN ARAH KARIR MAHASISWA - ., Alfaiz; ., Daharnis; ., Syahniar (Konselor, 2013)
This research was based on a pre-observation at the STIT Syekh Burhanuddin Pariaman. Which, the students were from difference background of education in high school, consisted of general schools and from religion schools, and actually they did not have clear orientation about self capabilities, self perception, personalities, learning, social and career with career they pursue. The purposes of this research were to described contribution self efficacy and self concept to career readiness and described the difference of self efficacy, self concept and career readiness among the students. Data were collected through a Likert scale questionaire and self efficacy scale adopted from Bandura, which was the validity and reliability has been tested. The data were analyzed by comparing means with independent sample t test and regression technique.